Community Archives in Australia: A Preliminary Investigation. Issue 4 (1st October 2020) - Gibbons, Leisa
ABSTRACT: The contemporary community archives movement is described as a grassroots social movement that evolved out of social, political and cultural change in the 1960s and 70s in the U.K. What is Australia's community archives story? In this exploratory essay, I set out to identify and examine who is talking about community archives in Australia and what they are (and are not) saying about it. Drawing from evidence obtained from web and literature searches, this paper highlights the complexity around the conversation about community archives in Australia.